Biblioteka ziemiańska na przykładzie biblioteki Ostrowskich i Potockich z Maluszyna - Rybka, Aleksandra (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The subject matter of books and libraries in 19th century is a very difficult issue. Gathering a domestic book collection was hard because of the difficult political situation. The fact that the Republic of Poland had been situated under the occupation caused a consciousness of collecting and passing down the Polish cultural heritage. The landowners had the best conditions to fulfill this aim because they had both financial and local facilities at their disposal. After a while, stately libraries gradually started to originate in courts and palaces, counting from a few hundred up to even a few hundred thousand items. Those which were the biggest ones were becoming foundational libraries, as the example of the National Ossolinski Institute Library, serving the whole society. The smaller ones were used by the owners, educated young people as well as local inhabitants. The Book Collection of Potocki and Ostrowski archived in Maluszyn is a good example of such a library. On the basis of the preserved inventories, which relate to a of a book collection, it is possible to recreate the library’s resources and determine its the most crucial functions. The state of the research for these days allows for conclusions that at that time this library belonged to the group of the biggest libraries in the region and that it was created with a thought of making it available to all inhabitants from local villages and towns, and that is the reason why it could fulfill an informal function of a public library. The following article presents the establishments concering laudowning libraries in 19th century as well as the reasons and ways of collecting, the use and the lot of the book collection, but most of all, the sources for researching laudowning book collection. Futhermore, there is also a current state of research on the library in Maluszyn mentioned.